2015
DOI: 10.1128/jvi.00097-15
|View full text |Cite
|
Sign up to set email alerts
|

CCCTC-Binding Factor Recruitment to the Early Region of the Human Papillomavirus 18 Genome Regulates Viral Oncogene Expression

Abstract: Host cell differentiation-dependent regulation of human papillomavirus (HPV) gene expression is required for productive infection. The host cell CCCTC-binding factor (CTCF) functions in genome-wide chromatin organization and gene regulation. We have identified a conserved CTCF binding site in the E2 open reading frame of high-risk HPV types. Using organotypic raft cultures of primary human keratinocytes containing high-risk HPV18 genomes, we show that CTCF recruitment to this conserved site regulates viral gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
111
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(122 citation statements)
references
References 70 publications
11
111
0
Order By: Relevance
“…Using HPV31 episome-containing cells as a model system, the Laimins group showed that CTCF was predominantly recruited to the late gene region and that depletion of CTCF, or mutation of the L2 binding site cluster resulted in reduced episome copy number and failure of episomal establishment [97]. Somewhat in contrast to these findings, our laboratory has shown that HPV18 genomes have enriched CTCF binding at the high-risk HPV-specific E2 ORF with an absence of binding in the late gene region, suggesting that different high-risk HPV types have evolved different strategies of gene expression control [52,98]. Mutation of the single E2-CTCF binding site in HPV18 had no effect on replication or maintenance of HPV18 episomes, but resulted in increased early transcript production and a concomitant increase in E6 and E7 protein expression and cellular hyperproliferation [98].…”
Section: Differentiation-dependent Regulation Of the Hpv Epigenomementioning
confidence: 74%
See 2 more Smart Citations
“…Using HPV31 episome-containing cells as a model system, the Laimins group showed that CTCF was predominantly recruited to the late gene region and that depletion of CTCF, or mutation of the L2 binding site cluster resulted in reduced episome copy number and failure of episomal establishment [97]. Somewhat in contrast to these findings, our laboratory has shown that HPV18 genomes have enriched CTCF binding at the high-risk HPV-specific E2 ORF with an absence of binding in the late gene region, suggesting that different high-risk HPV types have evolved different strategies of gene expression control [52,98]. Mutation of the single E2-CTCF binding site in HPV18 had no effect on replication or maintenance of HPV18 episomes, but resulted in increased early transcript production and a concomitant increase in E6 and E7 protein expression and cellular hyperproliferation [98].…”
Section: Differentiation-dependent Regulation Of the Hpv Epigenomementioning
confidence: 74%
“…Somewhat in contrast to these findings, our laboratory has shown that HPV18 genomes have enriched CTCF binding at the high-risk HPV-specific E2 ORF with an absence of binding in the late gene region, suggesting that different high-risk HPV types have evolved different strategies of gene expression control [52,98]. Mutation of the single E2-CTCF binding site in HPV18 had no effect on replication or maintenance of HPV18 episomes, but resulted in increased early transcript production and a concomitant increase in E6 and E7 protein expression and cellular hyperproliferation [98]. Importantly, we showed that CTCF-mediated repression of HPV early gene transcription via the stabilization of a chromatin loop formed between the E2 ORF and the URR.…”
Section: Differentiation-dependent Regulation Of the Hpv Epigenomementioning
confidence: 77%
See 1 more Smart Citation
“…Many excellent studies have been carried out with primary human keratinocytes to characterize the immortalization properties of high risk HPV (HR-HPV) These HPV immortalized cells have proved invaluable at identifying cellular proteins that are required for the life cycle of HR-HPV (36, 2943). For example, it is clear that host cell homologous recombination factors are required for the amplification phase of the viral life cycle (5, 39, 40).…”
Section: Discussionmentioning
confidence: 99%
“…For EBV and KSHV, CTCF mediates the recruitment of cohesins and the formation of higher-order DNA conformational structures that have been implicated in regulating the latent to lytic switch, and latency-associated transcription programming. Recent studies with HPV reveal that CTCF regulates the alternative splicing of viral RNA transcripts (Paris et al, 2015), as well as the recruitment of the cohesin subunit SMC1 required for viral genome amplification. CTCF can also bind to the proviral genome of the retrovirus HTLV-1 to regulate RNA splicing, epigenetic boundaries, and the antisense transcription of the viral HBZ gene, necessary for clonal persistence (Satou et al, 2016).…”
Section: Epigenetics and Viral Chromatinmentioning
confidence: 99%